A model of differentiation in quantum bioinformatics. (November 2017) - Asano, Masanari; Basieva, Irina; Khrennikov, Andrei; Yamato, Ichiro
Abstract: Differentiation is a universal process found in various phenomena of nature. As seen in the example of cell differentiation, the creation diversity on individual's character is caused by environmental interactions. In this paper, we try to explain its mechanism, which has been discussed mainly in Biology, by using the formalism of quantum physics. Our approach known as quantum bioinformatics shows that the temporal change of statistical state called decoherence fits to describe non-local phenomena like differentiation.